The Ordeals of Mountaineering Responders in Santa Cruz, Davao del Sur: A Phenomenological Study - Araña, Khezziah Bianca; Apas, Roel Jr. (Journal of Interdisciplinary Perspectives, 2025)
This phenomenological study explored the lived experiences, coping mechanisms, and memorable insights of eight mountaineering responders from Barangays Astorga and Darong in Santa Cruz, Davao del Sur. Through the process of personal experience description, listing of textual description, grouping relevant topics, writing textual description, writing structural description, and identifying the essence of the phenomenon, the collected data was examined and deduced. A data analyst assisted the development of key subjects, and the results show that the lived experiences of the Astorga Mountaineer Ecological Conservation Club and Rescue Team (AMECC ART) in dealing with disaster include being equipped to respond to various situations and trained to serve people. Moreover, the coping mechanism of the AMECC ART, as a responsive responder, emphasizes the need to join training and workshops, apply various strategies or techniques, and trust fellow responders. In addition, the memorable insights/training programs of the AMECC ART responder’s journey as a responsible responder are teammates, personal goals, learning from the pro, and overcoming difficulties at times. It is recommended that an Ordinance be implemented for the Municipal Disaster Risk Reduction Management Office (MDRRMO) of Santa Cruz, Davao del Sur, proposing a budget identifying the needs, equipment, and financial subsidy for better disaster resources and response. Additionally, a leadership training will be provided for the Officials of the AMECC ART.